Navigating diagnostic dilemmas: Localizing parathyroid adenoma in the presence of MIBI-avid thyroid nodules: A case report and literature review - Zohreh Maghsoomi; Maryam Rafieemanesh; Atefeh kashanizadeh; Behnaz Boozari; Mohammad Reza Babaei; Neda Hatami; Mohammad E․ Khamseh; Mehran Arab-Ahmadi (Radiology Case Reports)
Surgery is the preferred treatment for primary hyperparathyroidism (PHPT), but the presence of MIBI-avid thyroid nodules can complicate the localization of parathyroid adenoma (PA). In this case report, we discuss the role of imaging in localizing PA in a patient with concurrent thyroid nodules. A 49-year-old female presented with hypercalcemia and elevated parathyroid hormone levels. Technetium-99m-sestamibi single-photon emission computed tomography/computed tomography (SPECT/CT) showed MIBI-avid enhancement in the left thyroid lobe. Neck ultrasonography revealed 3 thyroid nodules in the left lobe, categorized as Thyroid Imaging Reporting and Data System (TI-RADS) 4. Fine-needle aspiration cytology yielded indeterminate results, and iPTH washout concentration was not elevated. Parathyroid 4-dimensional computed tomography (4D CT) was performed, which revealed an extra thyroid lesion on the left side, favoring PA. Left thyroid lobectomy and parathyroidectomy were performed, and the pathology report confirmed PA and follicular thyroid carcinoma. In cases where MIBI-avid thyroid nodules mimic PA, a combination of imaging modalities including technetium-99m-sestamibi SPECT/CT, neck ultrasonography, and parathyroid 4D CT can aid in differentiating between intrathyroid PA and extrathyroidal locations. Accurate preoperative localization is crucial for successful surgical management of PHPT. These imaging techniques play a pivotal role in guiding surgical decisions and ensuring optimal patient outcomes.